Poverty Among Fishing Households in the Coastal Area of West Sekotong, West Lombok Regency from the Perspective of Maqashid Syari'ah - Karomatul Ulya; Ihsan Ro’is; Akhmad Jufri (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze poverty among fishermen households in the coastal area of West Sekotong Beach, West Lombok Regency, using a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving key informants, main informants, and additional informants. The data analysis technique was carried out through data reduction, data presentation, and conclusion drawing using triangulation to test the validity of the data. The results of the study indicate that all informants are classified as poor and do not fall into the categories of masakin or maskanah, because the poverty experienced is not caused by a total inability to fulfill basic living needs, but rather by structural barriers, limited optimization of economic potential, lack of business diversification, and inadequate access to resources. From the perspective of Maqashid Shari’ah, the condition of the fishing communities generally fulfills the five main objectives of Islamic law, namely the protection of religion (hifz ad-din), protection of life (hifz an-nafs), protection of intellect (hifz al-‘aql), protection of lineage (hifz an-nasl), and protection of wealth (hifz al-mal). However, these fulfillments remain at the level of basic needs and have not yet reached the level of prosperity or well-being. This condition can be seen from the existing limitations in consistently performing religious practices, lack of attention to education, low family economic management, and limited access to business capital that complies with Sharia principles.